Respons Petani Padi Terhadap Minat Dan Kemungkinan Menanam Hanjeli di Kecamatan Buahdua Kabupaten Sumedang - Wiyono, Sulistyodewi Nur; Utami, Hesty Nurul; Salsabila, Dita Nur; Nurmala, Tati; Wicaksono, Fiky Yulianto (Universitas Galuh, 2025)
Sumedang Regency is one of the regions in West Java with relatively low rice production compared to Karawang, Indramayu, and Subang Regencies. The low productivity of rice farming in Sumedang presents an opportunity to introduce functional food crops as an alternative source of income for rice farmers. This study aims to analyze the characteristics of rice farmers and their current farming practices, as well as to examine their interest and likelihood of cultivating hanjeli as an alternative crop. A descriptive statistical approach was employed, using survey and questionnaire methods distributed to 65 respondents in Buahdua District, Sumedang Regency. The results indicate that the majority of rice farmers are male, aged between 40–60 years, and married. Most have completed elementary school, do not own land, and cultivate less than 0.5 hectares. Their average farming income is IDR 1.4 million per month, with an average monthly production cost of IDR 1.8 million. The findings reveal that the interest of rice farmers in cultivating hanjeli remains low. Most farmers are not yet confident in the economic potential of hanjeli as a supplementary income source. However, a small number of farmers show a potential willingness to adopt hanjeli cultivation, suggesting that with proper intervention and market support, adoption could increase over time.